A Novel Splicing Mutation in the CSF1R Gene in a Family With Hereditary Diffuse Leukoencephalopathy With Axonal Spheroids - Yang, Xiaodong; Huang, Pei; Tan, Yuyan; Xiao, Qin (Frontiers in Genetics, 2019)
Hereditary diffuse leukoencephalopathy with axonal spheroids (HDLS) is a rare autosomal dominant disorder that typically presents with early-onset cognitive decline or personality change. The disease is associated with heterozygous mutations in the colony stimulating factor-1 receptor (CSF1R) gene. CSF1R activation regulates microglial survival, proliferation and differentiation. The different gene mutations may be related to the various clinical phenotypes. Here, we described comprehensive clinical, neuroimaging, neuropathological and genetic analyses of a family with HDLS. A novel splicing mutation in intron 13 (c.1858+1G>T) of CSF1R was found in this family. It is located at the splice site of intron 13, resulting in a splice donor site leading to exon 13 skipping from the CSF1R mRNA. The mother and two elderly siblings of the proband had the same CSF1R mutation as the proband but showed very mild neuroimaging abnormalities and mild memory loss, which did not affect daily life, indicating very uneven penetrance and distinctly different disease progression among family members. This report provides diverse neuroimaging and clinical characteristics of a novel CSF1R mutation with different disease penetrance. The large clinical heterogeneity in the same family who all had the same mutation indicates that modifying genes and environmental factors may play a role in the pathogenesis of HDLS.